The Effect of Leverage, Profitability and Capital Intensity on Tax Aggressiveness in the Technology Sector - Agnes Dewi Septiani; Ginatun Ilmah; Tika Septiani (Облік і фінанси)
Since taxes are part of the income paid to the state, businesses often seek to reduce their tax liabilities using various methods. In this context, tax aggression means taking every legal avenue to minimize tax liability. This study aims to assess the impact of leverage, profitability, and capital intensity on tax aggressiveness of technology sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The methodology of this study is quantitative and involves conducting multiple linear regression analysis. The sample comprises 11 companies from the technology industry, chosen using purposive sampling. This study uses secondary data from companies' financial reports published on the IDX website. The data was analyzed using the SPSS 21 software. In this study, tax aggressiveness is represented by the effective tax rate (ETR), which considers all taxes paid relative to total income or profit. The debt-to-equity ratio (DER) was used to evaluate a company's financial leverage and the return on assets (ROA) – to evaluate a company's profitability. Capital intensity refers to the ratio obtained by comparing the fixed assets to the total assets of a business. The results demonstrate that leverage does not substantially affect tax aggressiveness. In contrast, profitability and capital intensity substantially negatively influence tax aggressiveness. This indicates that companies with increased capital investment in fixed assets typically incur higher depreciation charges, diminishing their taxable revenue and, subsequently, their tax liability. Conversely, increased profitability diminishes tax aggressiveness, as financially robust organizations are less likely to engage in aggressive tax planning tactics. After all, analysis showed that the factors selected for this study account for only 19% of the variation in tax aggressiveness. Therefore, future studies should assess the impact of other factors to better understand the phenomenon of tax aggressiveness.